2017
DOI: 10.1007/s00334-017-0602-6
|View full text |Cite|
|
Sign up to set email alerts
|

A methodological approach to the study of archaeological cereal meals: a case study at Çatalhöyük East (Turkey)

Abstract: This paper presents an integrated methodology for the analysis of archaeological remains of cereal meals, based on scanning electronic microscopic analyses of microstructures of charred food fragments from Neolithic Çatalhöyük (Turkey). The remains of cereal foods as ‘bread-like’ or ‘porridge-like’ small charred lumps of various amalgamated plant materials are frequently recovered from Neolithic and later archaeological sites in southwest Asia and Europe. Cereal food remains have recently attracted interest be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 48 publications
2
46
1
Order By: Relevance
“…7) -fostered different tastes and identities. Study of charred amorphous fragments of foodstuffs indicates the preparation of batters and breads throughout the East Mound sequence but with increasing preparations of cereal-based porridges in the latest (TP/TPC) levels (Gonzalez Carretero et al 2017). Diachronic trends also imply changing priorities in the organisation of daily tasks, with less time devoted to frequent, labour-intensive processing activities such as soaking the toxins from bitter vetch seeds or dehusking glume wheats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7) -fostered different tastes and identities. Study of charred amorphous fragments of foodstuffs indicates the preparation of batters and breads throughout the East Mound sequence but with increasing preparations of cereal-based porridges in the latest (TP/TPC) levels (Gonzalez Carretero et al 2017). Diachronic trends also imply changing priorities in the organisation of daily tasks, with less time devoted to frequent, labour-intensive processing activities such as soaking the toxins from bitter vetch seeds or dehusking glume wheats.…”
Section: Discussionmentioning
confidence: 99%
“…The tubers (and nutlets) of sedges, especially Bolboschoenus glaucus, are ubiquitous throughout the sequence. The nutlets are at least partly derived from the burning of animal dung as fuel (Bogaard et al 2013), while the tubers may have been collected as food, as a few examples have been found embedded in cereal-based, bread-like food remains (Gonzalez Carretero et al 2017), and were probably consumed fresh, given their absence from 'storage' deposits (Fairbairn et al 2005;. Figure 13 summarises proportions of fruit/nut taxa through time, revealing continuity in use of hackberry (preserved in the absence of charring due to its silica-rich shell) and pistachio.…”
Section: Diachronic Trends In Cereal and Pulse Cropsmentioning
confidence: 99%
“…They compared macroscopic techniques to physicochemical techniques and specifically demonstrated that different methods of cooking change the structure of bones. Examining the microstructures of charred food remains using SEM (scanning electron microscopy), especially in conjunction with experimental archaeology (Carretero et al 2017) or chemical analysis (Kubiak-Martens et al 2015), helps identify particular foods and how they were cooked. Without charring, starch grains can be difficult to see.…”
Section: Methodsmentioning
confidence: 99%
“…Many archaeologists interested in the different actions, ingredients, and tools involved in preparing food use experimental archaeology to learn more about different choices and steps in processes that may no longer be visible. Some researchers use experiments with food and tools to look for identifiable ways that certain food preparation techniques might be visible archaeologically (Carretero et al 2017;Capparelli et al 2015;Dezendorf 2013;Disspain et al 2016;Fernandes et al 2014;Graesch et al 2014;Gur-Arieh et al 2012;Hart et al 2007;Henry et al 2009;Müller et al 2013;Pecci et al 2013;Raviele 2011;Simms et al 2013;Thoms 2008;Warinner and Tuross 2009). For example, Morrison et al (2015) combined experimental archaeology with ceramic analysis and archaeological, zooarchaeological, ecological, and ethnographic data.…”
Section: Experimental Archaeologymentioning
confidence: 99%
See 1 more Smart Citation